A COMPARISON ON MOTIVATION IN LEARNING ENGLISH BETWEEN WHO TAUGHT BY USING PICTURE STORIES AND WHO TAUGHT BY USING CONVENTIONAL TECHNIQUE OF THE SECOND YEAR STUDENTS' OF MADRASAH TSANAWIYAH DARUL HIKMAH PEKANBARU - Muhammad Ari Saputra (SALEE: Study of Applied Linguistics and English Education, 2020)
The research has three formulations of the problem that how students’ motivation in learning English taught by using conventional technique is, how students’ motivation in learning English taught by using picture sories is, and whether or not there is a significant difference of students’ motivation in learning English between students who are taught by using conventional technique and those taught by using picture stories. This research is causal-comperative research. There are two variables in this research. They are x variable (using picture stories) as independent variable and y variable (students’ motivation in learning English) as dependent variable. Based on the writer’ preliminary study of the second year students of Madrasah Tsanawiyah Darul Hikmah Pekanbaru, showed that students’ motivation in learning English was low. The writer had tried to solve this problem by implementing the picture stories as media. The pictures were one of the media in teaching and learning process that could be implemented to the students in learning English. The objective of this research was to find out whether there was a significance difference of using picture stories toward students’ motivation in learning English. The sample of this research was the second year students of Madrasah Tsanawiyah Darul Hikmah Pekanbaru. The writer used observation and questionnaire to collect the data of this research. The data were analyzed by using T-test. Having analyzed the data with independent sample T-test, it can be seen that there is a significance difference between using picture stories and conventional technique toward motivation in learning English of the second year students’ of Madrasah Tsanawiyah Pekanbaru. It was provided by finding t0 (3.510), which is greater than t-table at 5% grade of significance (2.04) and at 1% grade significance (2.76). And to = 3.510 is higher than ttabel from sig. 5% and 1% (2.04 < 3.510 > 2.76). It means there is significance difference between students’ motivation by using picture stories and conventional technique.